Rule-Of-Thumb Consumers, Productivity and Hours - Francesco Furlanetto; Martin Seneca (Norges Bank, 2007)
In this paper we study the transmission mechanisms of productivity shocks in a model with rule-of-thumb consumers. In the literature, this financial friction has been studied only with reference to fiscal shocks. We show that the presence of rule-of-thumb consumers is also very helpful in accounting for recent empirical evidence on productivity shocks. Rule-of-thumb agents, together with nominal and real rigidities, play an important role in reproducing the negative response of hours and the delayed responses of output and consumption after a productivity shock.
hdl:11250/2498271
Keywords: E32; 330; rule-of-thumb consumers; productivity shocks; nominal rigidities; real rigidities